2010
DOI: 10.1007/s00428-010-0901-0
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD10 (56C6) is expressed variably in adrenocortical tumors and cannot be used to discriminate clear cell renal cell carcinomas

Abstract: In the evaluation of retroperitoneal masses, the practicing pathologist faces a dilemma when making a diagnosis based on histology given the often overlapping morphologic appearances of the adrenocortical carcinoma, renal cell carcinoma (RCC), and hepatocellular carcinoma (HCC). CD10 is expressed in a membranous fashion in the vast majority of clear cell RCCs; therefore, it is widely used for distinction from its mimics. However, its expression is not well-investigated in adrenal cortical tumors. We examined C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…CD10, for instance, can show variable expression in papillary thyroid carcinomas as well in tumors from adrenocortical origin. 23,24 Likewise, PAX8 can be frequently positive in primary thyroid neoplasms. 25 Therefore, ICC stains should always be interpreted as a panel and in light of clinical data (Table).…”
Section: Metastatic Renal Cell Carcinomamentioning
confidence: 99%
“…CD10, for instance, can show variable expression in papillary thyroid carcinomas as well in tumors from adrenocortical origin. 23,24 Likewise, PAX8 can be frequently positive in primary thyroid neoplasms. 25 Therefore, ICC stains should always be interpreted as a panel and in light of clinical data (Table).…”
Section: Metastatic Renal Cell Carcinomamentioning
confidence: 99%
“…12 Caution, however, has been expressed with regard to the use of CD10, as it may also react with adrenocortical tumors and is therefore not a specific marker of clear cell RCC. 25 Another study found antisteroidogenic factor-1, calretinin, inhibin, and melan-A to be indicative of an adrenocortical origin, whereas anti-human kidney injury molecule-1 (hKIM-1), Pax 8, hepatocyte nuclear factor-1b, EMA, and CAIX were valuable in establishing a tumor as a clear cell RCC. 8 …”
Section: Diagnosis Of Renal Cell Neoplasiamentioning
confidence: 99%
“…Sin embargo, se debe tomar con cautela la expresión de CD10, ya que también puede aparecer en tumores adrenocorticales y, por lo tanto, no se puede considerar un marcador específico de CCR de células claras (463).…”
Section: 22311neoplasias De Células Renales Frente a Neoplasias No Células Renalesunclassified